How UUM accounting students learn - Ali, Amin; Abas, Zakaria; Abdul Jabbar, Hijattulah (Sekolah Perakaunan, Universiti Utara Malaysia, 2000)
Learning is the process whereby knowledge in created through the transformation of experience. Previous studies claimed that learning has taken place when either or both of these conditions apply. First is when the individual knows something new and secondly, when he/she can do something previously he/she cannot. Learning is a non-stop process and it needs skill. As noted in the literature, every person has a different influencing factors.